2000
DOI: 10.1093/ndt/15.9.1414
|View full text |Cite
|
Sign up to set email alerts
|

Three monocyte‐related determinants of atherosclerosis in haemodialysis

Abstract: Patients on haemodialysis have an increased systemic chemotactic activity for monocytes, unphysiological phenotypic alterations in CD11b/ CD18 expression during and after dialysis, and increased sVCAM-1 and MCP-1 concentrations. Prospective studies are needed to establish the role of these abnormalities in the pathogenesis of atherosclerosis in haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
5
15
0
3
Order By: Relevance
“…The plasma concentration of MCP-1 was increased significantly in PD and HD patients, and the plasma concentration of soluble TGF-␤ was increased in HD patients only, confirming previous reports (33)(34)(35)(36). MCP-1 is associated with macrophage infiltration into the peritoneal cavity of PD patients and correlates with soluble adhesion molecule expression in HD (33,37).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The plasma concentration of MCP-1 was increased significantly in PD and HD patients, and the plasma concentration of soluble TGF-␤ was increased in HD patients only, confirming previous reports (33)(34)(35)(36). MCP-1 is associated with macrophage infiltration into the peritoneal cavity of PD patients and correlates with soluble adhesion molecule expression in HD (33,37).…”
Section: Discussionsupporting
confidence: 90%
“…MCP-1 is associated with macrophage infiltration into the peritoneal cavity of PD patients and correlates with soluble adhesion molecule expression in HD (33,37). TGF-␤ is a key mediator of renal fibrosis in progressive renal failure and ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, there have been few studies of the relationship between the severity of human atherosclerosis and the serum concentration of MCP-1 in HD patients. 13,14 High-resolution ultrasound imaging is now a reliable means of directly examining and quantifying pre-clinical Circulation Journal Vol. 68, July 2004 atherosclerotic lesions in peripheral arteries.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] In the clinical setting, it has been reported that the plasma concentrations of several cytokines and chemokines, including MCP-1, increased during long-term HD treatment. 13 However, there have been few studies of the relationship between the severity of human atherosclerosis and the serum concentration of MCP-1 in HD patients. 13,14 High-resolution ultrasound imaging is now a reliable means of directly examining and quantifying pre-clinical Circulation Journal Vol.…”
mentioning
confidence: 99%
“…Dialysis can reduce leukocyte-endothelial interactions and impair transmigration (Thylen et al 1997). In patients on hemodialysis with cuprophane or polysulfone membranes, a significantly higher serum level of MCP-1 is seen compared with healthy subjects both before and after the hemodialysis session, independent of the membrane used (Jacobson et al 2000;Thylen et al 2000). Biocompatibility of dialysis membranes probably plays an important role in determining leukocyte function in patients on hemodialysis (Himmelfarb et al 1991;Himmelfarb et al 1993;Hernandez et al 2004;Schindler et al 2006).…”
Section: Patients On Hemodialysismentioning
confidence: 99%